Effect of Interest Rate on Stock Prices in Ghana - Arhenful, Peter; Yeboah, Augustine Kwadwo; Adjei, Kofi Sarfo (Journal of Social and Development Sciences, 2021)
The paper assesses the effect of interest rate on stock prices, with emphases on Ghana Stock Exchange; using monthly time series data from July 2007 to December 2019. The Augmented Dickey-Fuller (ADF) test was employed to establish the stationarity properties of the data or otherwise. Using the Ordinary Least Squares (OLS) estimation technique of Multiple Regression, the results (? = – 0.891, p < 0.05) revealed an indirect association between interest rates and stock prices in the Ghanaian context; which is consistent with the theoretical conclusion that an increase in interest rate results in a decrease in stock prices. Thus, in the light of this finding, it was recommended that policymakers should consider the stock market dynamics due to the significant relationship that exists between the two macroeconomic variables.